Importance-performance analysis to inform visitor management at marine wildlife tourism destinations - Simpson, Greg D.; Patroni, Jessica; Teo, Albert C.K.; Chan, Jennifer Kim Lian; Newsome, David (Emerald Group Publishing Ltd, 2020)
Purpose – The purpose of this paper is to postulate that the technique of Importance-Performance Analysis (IPA) is currently underutilised in visitor management studies reported in the peer-reviewed marine wildlife tourism (MWT) research literature. Further, this paper provides insight into how IPA could inform future research and management of tourism experiences at marine wildlife destinations. Design/methodology/approach – This paper synthesises learning gained from the natural area tourism and recreation literature that report the application of IPA in MWT and insights from a recent study at the Dolphin Discovery Centre in Bunbury, Western Australia. Findings – Although currently underutilized in MWT research, IPA is a relatively straightforward, easy to interpret, and, if correctly applied, a powerful tool that managers and researchers can employ to investigate and enhance visitor satisfaction in the short-term and for longer-term sustainability of the industry through visitor-informed tourism management. Originality/value – Having identified the opportunity to enhance visitor experiences, site management and target species welfare through increased IPA research, this review provides a plain language introduction to the application of IPA and direct access to comprehensible academic discourses and exemplars for the technique. Moreover, in light of increasing tourism demand, IPA can assist in determining management options for the future.